A longitudinal study on the professional identity formation of health promotion practitioners: evidence from undergraduate students in Switzerland - Biehl, Verena; Bänziger, Andreas; Wieber, Frank (Frontiers in Medicine, 2025)
IntroductionProfessional identity (PI) is crucial for workforce capacity building, as it leads to the adoption of the professional role and commitment. And yet, there is little literature on the PI of health promotion practitioners as part of the public health workforce. Education plays a significant role in PI formation. Therefore, the aim of this study is to investigate PI formation in undergraduate health promotion students. To conceptualize PI, we draw on social psychological theories and consider potential determinants across cognitive, social, motivational, and behavioral dimensions.MethodsTo gain insights into the PI formation of health promotion students, an observational longitudinal study was conducted using an online survey at three times of measurement. Undergraduate physiotherapy students served as the comparison group. The outcome variable of PI was calculated as a composite score with three subscales. In addition to sociodemographic data, potential determinants in cognitive, social, motivational, and behavioral dimensions were measured. Mixed effect models were used to analyze these determinants of PI formation.ResultsThe study included 276 participants. On average, PI in health promotion students was moderate and declined over the course of the undergraduate program. In contrast, PI in physiotherapy students was high from the beginning and remained stable throughout their studies. Factors such as gender, self-esteem, insecurity about the study program, the perceived social status of the profession, and planned behavior during and after the program were found to influence health promotion students’ PI formation.DiscussionUndergraduate health promotion students lack a strong PI, especially compared to physiotherapy students. Given the importance of a strong PI, the following interventions are suggested to strengthen health promotion students’ PI: (1) incorporating PI formation as a learning objective within curricula, and (2) enhancing the visibility and clarity of health promotion’s professional profile within undergraduate studies and in society. By recognizing the factors that shape PI and implementing targeted interventions, stakeholders can empower the next generation of health promotion practitioners to navigate their professional journeys with confidence and purpose, thereby strengthening workforce capacity building in health promotion.